ANALISIS FAKTOR PENENTU KEPUTUSAN PEMBELIAN IKAN HIAS DI PUSAT PROMOSI IKAN HIAS KOTA BEKASI - Cahyati, Cici; Budiyono, Haris; Kamilah, Ahya (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2024)
Ornamental Fish Promotion Center is a place for ornamental fish’s sellers which are managed by the Dinas Ketahanan Pangan, Pertanian, dan Perikanan of Bekasi City. It is important for sellers to knows what influences consumers in purchasing decisions. This study aims to determine (1) influence of colour to ornamental fish purchasing decision (2) influence of shape to ornamental fish purchasing decision (3) influence of fish care to ornamental fish purchasing decision (4) influence of feeding to ornamental fish purchasing decision (5) influence of life to ornamental fish purchasing decision This study uses survey methods and data analysis used was multiple linear regression analysis. The results showed that color had an effect on the purchase decision of ornamental fish, shape had an effect, maintenance had an effect, feed had no effect on the purchase decision on ornamental fish, and vitality had an effect on the purchase decision on ornamental fish. Variables of color, shape, maintenance, feed, and vitality together influence the decision to buy ornamental fish at the Ornamental Fish Promotion Center in Bekasi City.